Microbial processes in relation to carbon, nitrogen and temperature regimes in litter and a sandy mineral soil from a central Siberian Pinus sylvestris L. forest - Ross, D.J.; Kelliher, F.M.; Tate, K.R. (Soil biology & biochemistry, 1999)
The coniferous forests of Siberia contain a significant fraction of the world's terrestrial C. We have assessed organic matter storage and potential metabolic activities in one of these forest stands by determining C and N pools, microbial properties and C and N mineralization at different temperatures in litter and a sandy mineral soil (a Pergelic Cryochrept) from a 215-y old forest of Pinus sylvestris L. Relationships between CO 2–C production in the laboratory and field were also assessed. The site was near Zotino in central Siberia at 61° N, 89° E and has an average air temperature of ca. −4°C and an annual precipitation of ca. 620 mm; it is subject to water deficits during summer and to recurrent fires. Results were evaluated by comparisons with data from other coniferous forests, including those with sandy or sandy loam soils at three temperate sites under Pinus radiata D. Don in New Zealand. The very acid (pH 4.1) litter (ca. 3 cm depth) from the Zotino site contained (to 50 cm depth of mineral soil) ca. 41% of the total C (2.8 kg m −2), 34% of the total N (86 g m −2) and about 50% of the microbial biomass and respiratory and net N-mineralizing activity. The low values in the mineral soil were, except for total N which was lowest at the Zotino site, generally similar to those in two young coastal sands under P. radiata in New Zealand. Rates of C and net N mineralization in the Zotino mineral soil declined proportionately more between 13.5°C and 5.5°C than between 25 and 13.5°C. Use of temperature relationships suggested that less than half of the CO 2–C produced from the soil profile in the field under well-watered conditions during summer would have originated from microbial respiration. In litter and in mineral soil, ratios of microbial C and N-to-total C and N, microbial C-to-microbial N, rates of CO 2–C and net mineral-N production on a total C and N basis, and metabolic quotients (qCO 2 values) were all similar to at least some of the values found for the temperate pine-forest soils. Our results strongly suggest that soil organic matter content is low at this Zotino site, not because of distinctive metabolic potentials of the microbial populations, but because of environmental constraints on ecosystem processes.